Mobile PET insert for simultaneous PET/MRI imaging. (September 2016) - Zielinski, Marcin; Alfs, D.; Bednarski, T.; Białas, P.; Czerwiński, E.; Gajos, A.; Głowacz, B.; Gorgol, M.; Jasińska, B.; Kamińska, D.; Korcyl, G.; Kowalski, P.; et al.
Abstract : Access to the anatomical and functional information about the body interior is possible with tomography techniques relying on the registration of radiation from the tissues. Modern medicine offers: Positron Emission Tomography, Magnetic Resonance and Computer Tomography. One of the present technological challenges is to combine the PET and MR scanners to work as single device to provide PET/MR images. Presented solution of a portable-PET scanner will allow simultaneous registration of PET and MR images utilizing existing MR scanners. The developed device is based on the strip-PET concept consisting of detection modules, each build from a plastic scintillator strip connected at both ends with silicon photomultipliers array. In the proposed solution determination of the point of annihilation along the direction of the gamma quanta flight path, is based on the time difference registered in various detection modules. It is important to stress that the utilized silicon photomultipliers are insensitive to the MR magnetic field. In order to position two tomographic images with respect to each other we will use watermarks, seen by MRI system. Since this method explicitly specify the position of the MRI with respect to PET scanner therefore it enables for synchronize both tomographic images. The advantage of this solution is to eliminate the possibility of artifacts in tomographic images hindering the identification of potentially cancerous lesions. In the talk we will present developed solution of a mobile-PET insert to MR scanners. The presentation will include the characteristics of a proposed device together with the advantages over present solutions.